Identification of dynamic undifferentiated cell states within the male germline - Hue M. La; Juho-Antti Mäkelä; Ai-Leen Chan; Fernando J. Rossello; Christian M. Nefzger; Julien M. D. Legrand; Mia De Seram; Jose M. Polo; Robin M. Hobbs (NATURE PUBLISHING GROUP, 2022)
The role of stem cells in tissue maintenance is appreciated and hierarchical models of stem cell self-renewal and differentiation often proposed. Stem cell activity in the male germline is restricted to undifferentiated A-type spermatogonia (A(undiff)); however, only a fraction of this population act as stem cells in undisturbed testis and A(undiff) hierarchy remains contentious. Through newly developed compound reporter mice, here we define molecular signatures of self-renewing and differentiation-primed adult Aundiff fractions and dissect A(undiff) heterogeneity by single-cell analysis. We uncover an unappreciated population within the self-renewing Aundiff fraction marked by expression of embryonic patterning genes and homeodomain transcription factor PDX1. Importantly, we find that PDX1 marks a population with potent stem cell capacity unique to mature, homeostatic testis and demonstrate dynamic interconversion between PDX1+ and PDX1-(Aundiff) states upon transplant and culture. We conclude that Aundiff exist in a series of dynamic cell states with distinct function and provide evidence that stability of such states is dictated by niche-derived cues.